Educational level and living arrangements are associated with dietary intake of red meat and fruit/vegetables: A Danish cross-sectional study. Issue 5 (July 2019) - Laursen, Ulla Bach; Johansen, Martin Berg; Joensen, Albert Marni; Lau, Cathrine Juel; Overvad, Kim; Larsen, Mogens Lytken
Aims: To evaluate the association between education and living arrangements and the intake of fish, red meat and fruit and vegetables. Methods : The study design was cross-sectional and conducted in Denmark in 2013. Participants filled in questionnaires about their educational level and living arrangements (living alone or with others) and dietary intake including fish, red meat, fruit and vegetables. Regression analyses were performed to assess the associations within 85, 456 randomly sampled healthy men and women who were at least 25 years old. Results : Length of education was statistically significant and positively associated with the intake of fruit and vegetables and negatively associated with the intake of red meat for both men and women. Men with a high level of education had a 187g/week (95% confidence interval: 199–175g/week) lower intake of red meat and a 109g/day (95% confidence interval: 102–117g/day) higher intake of fruit and vegetables than men with a low level of education. Women with a high level of education had a 175g/week (95% confidence interval: 186–164g/week) lower intake of red meat and a 106g/day (95% confidence interval: 97–114g/day) higher intake of fruit and vegetables than women with a low level of education. Living with others was statistically significant and positively associated with the intake of red meat, and fruit and vegetables. There were no clear associations between education, living arrangements and intake of fish. Conclusions : Men and women with a high educational level ate more fruit and vegetables but less red meat than men and women with a low educational level. Men and women living with others ate more red meat, fruit and vegetables than men and women living alone.